COVID-19 Clinical Characteristics, and Sex-Specific Risk of Mortality: Systematic Review and Meta-Analysis - Nasiri, Mohammad Javad; Haddadi, Sara; Tahvildari, Azin; Farsi, Yeganeh; Arbabi, Mahta; Hasanzadeh, Saba; Jamshidi, Parnian; Murthi, Mukunthan; Mirsaeidi, Mehdi (Frontiers in Medicine, 2020)
Background: The rapidly evolving coronavirus disease 2019 (COVID-19), was declared a pandemic by the World Health Organization on March 11, 2020. It was first detected in the Wuhan city of China and has spread globally resulting in a substantial health and economic crisis in many countries. Observational studies have partially identified different aspects of this disease. There have been no published systematic reviews that combine clinical, laboratory, epidemiologic, and mortality findings. Also, the effect of gender on the outcomes of COVID-19 has not been well defined. Methods: We reviewed the scientific literature published from January 1, 2019 to March 3, 2020. Statistical analyses were performed with STATA (version 14, IC; Stata Corporation, College Station, TX, USA). The pooled frequency with 95% confidence intervals (CI) was assessed using random effect model. P <0.05 was considered a statistically significant publication bias. Results: Out of 1102 studies, 32 satisfied the inclusion criteria. A total of 4789 patients with a mean age of 49 years were evaluated. Fever (83.0%, CI 77.5-87.6) and cough (65.2%, CI 58.6-71.2) were the most common symptoms. The most prevalent comorbidities were hypertension (18.5 %, CI 12.7-24.4) and Cardiovascular disease (14.9 %, CI 6.0-23.8). Among the laboratory abnormalities, elevated C-Reactive Protein (CRP)(72.0%, CI 54.3-84.6) and lymphopenia (50.1%, CI 38.0-62.4) were the most common. Bilateral ground-glass opacities (66.0%, CI 51.1-78.0) was the most common CT scan presentation. The pooled mortality rate was 6.6%, with males having significantly higher mortality compared to females (OR 3.4; 95% CI 1.2-9.1, P = 0.01). Conclusion: COVID-19 commonly presented subjectively with a progressive course of cough and fever with more than half of hospitalized patients displaying leukopenia or an elevated CRP. Mortality associated with COVID-19 was higher than that reported in studies done in China, with Males having a 3-fold higher risk of mortality compared to females.